LncRNAs associated with glioblastoma: From transcriptional noise to novel regulators with a promising role in therapeutics - Bhupender Yadav; Sonali Pal; Yury Rubstov; Akul Goel; Manoj Garg; Marat Pavlyukov; Amit Kumar Pandey (Elsevier, 2021)
Glioblastoma multiforme (GBM) is the most widespread and aggressive subtype of glioma in adult patients. Numerous long non-coding RNAs (lncRNAs) are deregulated or differentially expressed in GBM. These lncRNAs possess unique regulatory functions in GBM cells, ranging from high invasion/migration to recurrence. This review outlines the present status of specific involvement of lncRNAs in GBM pathogenesis, with a focus on their association with key molecular and cellular regulatory mechanisms. Also, we highlighted the potential of different novel RNA-based strategies that may be beneficial for therapeutic purposes.